Progress or stagnation? Is neurosurgery remaining a men’s world? - Marion Rapp; Laura Makowski; Franziska Staub-Bartelt; Julia Steinmann; Michael Sabel (Medical Education Online)
Although the number of female medical school students is increasing, there is an imbalance regarding women in neurosurgery. In addition, a huge gender gap concerning leading positions as well as scientific careers exists. We performed a questionnaire-based data assessment of former and current neurosurgical residents, medical school students in their final and medical school students in their first year. The questionnaire assessed reasons for resigning from the residency program as well as possible discrimination or gender-specific disadvantages which prevent medical school students from choosing a surgical speciality. We found that significantly more (p = 0.05) female residents left neurosurgical training and indicated gender-based inequalities during the program (p < 0.001). Significantly fewer final-year students would choose a surgical career compared to first-year medical students (p < 0.001). The main reasons against neurosurgical training were poor work-life balance, psychological stress and difficulties in family/child care. Women must continue to be supported to pursue surgical and scientific careers.